2014
DOI: 10.3171/2014.8.jns1447
|View full text |Cite
|
Sign up to set email alerts
|

Widening of the basilar bifurcation angle: association with presence of intracranial aneurysm, age, and female sex

Abstract: Object. Arterial bifurcations represent preferred locations for aneurysm formation, especially when they are associated with variations in divider geometry. The authors hypothesized a link between basilar apex aneurysms and basilar bifurcation (a) and vertebrobasilar junction (VBJ) angles.Methods. The a and VBJ angles were measured in 3D MR and rotational angiographic volumes using a coplanar 3-point technique. Angle a was compared between age-matched cohorts in 45 patients with basilar artery (BA) aneurysms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 27 publications
(40 reference statements)
5
47
0
Order By: Relevance
“…Importantly, non-aneurysmal MCA bifurcations analyzed in our present study had significantly higher values of α angle than the control bifurcations. These results correspond to those reported by other authors, according to whom patients with aneurysms presented with significantly wider non-aneurysmal bifurcation angles than the healthy controls 14,38 . This implies that persons with aneurysms might also show significant alterations in vascular dimensions and bifurcation angles of other arteries, and thus, might be predisposed to formation of de novo or multiple aneurysms.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Importantly, non-aneurysmal MCA bifurcations analyzed in our present study had significantly higher values of α angle than the control bifurcations. These results correspond to those reported by other authors, according to whom patients with aneurysms presented with significantly wider non-aneurysmal bifurcation angles than the healthy controls 14,38 . This implies that persons with aneurysms might also show significant alterations in vascular dimensions and bifurcation angles of other arteries, and thus, might be predisposed to formation of de novo or multiple aneurysms.…”
Section: Discussionsupporting
confidence: 92%
“…3D rotational angiography, MRA, CTA) dealing with the problem of bifurcation angle morphology showed that wide bifurcation angle constitutes a significant risk factor for aneurysm formation. Those studies included the bifurcations which are generally considered to be predisposed for aneurysm development: ACoA complex 8,16,[34][35][36] , BA 14,29,37 and MCA 30,38 . Our findings are consistent with the results of the studies mentioned above; our present study showed that Φ 1 , Φ 2 and α angles in aneurysmal MCA bifurcations were significantly wider than in contralateral and control bifurcations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Aneurysm presence at cerebral bifurcations was recently shown to be associated with wider bifurcation angles in both middle cerebral and basilar bifurcations. 1,21,25 Basilar bifurcations may widen with age, more so in women, possibly triggering tissue degeneration due to changes in the local hemodynamic environment. 25 Although the mechanism for aneurysm initiation is not completely understood, consensus is building regarding the disruptive role of local high WSS and high positive WSSG in the pathological process of aneurysm origination.…”
mentioning
confidence: 99%
“…1,21,25 Basilar bifurcations may widen with age, more so in women, possibly triggering tissue degeneration due to changes in the local hemodynamic environment. 25 Although the mechanism for aneurysm initiation is not completely understood, consensus is building regarding the disruptive role of local high WSS and high positive WSSG in the pathological process of aneurysm origination. 5,6,17,24 Studies in animals subjected to unilateral or bilateral common carotid artery ligation have shown that, without other known predisposing factors, flow increase alone at cerebral bifurcations can lead to EC remodeling consistent with aneurysm initiation.…”
mentioning
confidence: 99%